The Role of Digital Communication via X in Increasing Tourist Visits to the Mandalika Area, Central Lombok Regency - Roihan, Adam; Suhadah, Suhadah; Sukarta, Sukarta (Borong Newinera Publisher, 2025)
Mandalika tourism serves as a key economic driver in Central Lombok, West Nusa Tenggara, contributing significantly to regional revenue. To boost tourist arrivals, the local government uses social media, particularly X, as a digital communication platform to promote the destination. This study explores the impact of X-based communication on tourists’ perceptions and decision-making, while also identifying factors that influence the effectiveness of destination promotion. A combination of qualitative and quantitative methods was employed, including a survey of thirty respondents from both within and outside Lombok and a content analysis of tourism-related X posts published between July - December 2024. The survey data were analyzed using descriptive statistics and multiple linear regression techniques. Findings demonstrate that X plays a significant role in shaping tourists’ perceptions and increasing awareness of Mandalika. Information relevance and visual content quality emerged as the most influential factors in travel decision-making. However, excessive posting frequency can lead to reduced interest, whereas positive engagement with content increases visitor attraction. Content analysis further reveals high engagement levels, with seventy five percent of posts reflecting positive sentiment and strong support from official accounts and local influencers. The study concludes that X is an effective promotional tool for tourism when supported by relevant, engaging, and data informed communication strategies. These results provide practical insights for tourism stakeholders and policymakers aiming to enhance digital marketing efforts in Mandalika and similar emerging destinations.